Access to Intrinsically Glucoside‐Based Microspheres with Boron Affinity. Issue 11 (27th March 2013) - Vogt, Andrew P.; Tischer, Thomas; Geckle, Udo; Greiner, Alexandra M.; Trouillet, Vanessa; Kaupp, Michael; Barner, Leonie; Hofe, Thorsten; Barner‐Kowollik, Christopher
Abstract Intrinsically glucoside‐based microspheres are prepared in olive oil via a water in oil inverse suspension polymerization. The microspheres are characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) microscopy, and X‐ray photoelectron spectroscopy (XPS), evidencing the intrinsic glucose character of the spheres. A novel boronic acid fluorescent molecule was subsequently conjugated to the microspheres in an aqueous environment, exhibiting the spatial and uniform distribution of glucoside as well as the affinity of the microspheres to bind with boron, evidenced via fluorescence spectroscopy measurements. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>